“ANÁLISIS DE LOS LUGARES GASTRONÓMICOS TRADICIONALES Y SU IMPORTANCIA PARA EL DESARROLLO SOCIOECONÓMICO DEL CANTÓN SANTO DOMINGO DE LOS COLORADOS, PROVINCIA DE SANTO DOMINGO DE LOS TSÁCHILAS” - Chauca Ushiña, Francisco Javier (2020)
This study showed an analysis within the cultural gastronomic tourism sector and its determinants; as this sector has influenced the growth of the economy in the canton of Santo Domingo de los Tsáchilas, which aims to highlight the potential that this industry could gain in the development and growth of the area. Considering this approach, this research project will demostrate how a traditional gastronomic guide can help develop the area from its origin; Subsequently, a more in-depth analysis made of the different mechanisms linked to tourism and the economy and what would be the factors that in turn influence tourism. This work presents a review of some empirical studies carried out in order to understand the behavior of the traditional gastronomic tourism sector within the economy and its impact on the contribution these places have to conserving the culture of the canton. In order to meet the objectives, we will start from this research with an introduction to the subject, followed by the first chapter where the problem statement, justification and the general and specific objectives included. In the second chapter is the theoretical framework or state of the art the which will define different concepts on the subject treated, in the third chapter we talk about the methodology, design, type, level, research methods, also the population and sample, and in the fourth chapter we will have the results and interpretation, conclusions, recommendations, bibliography and annexes.